Ship English Sailors' speech in the early colonial Caribbean - Delgado, Sally (Language Science Press, 2019)
This book presents evidence that Ship English of the early Atlantic colonial period was a distinct variety with characteristic features. It is motivated by the recognition that late-seventeenth and early-eighteenth century sailors' speech was potentially an influential variety in nascent creoles and English varieties of the Caribbean, yet few academic studies have attempted to define the characteristics of this speech. Therefore, the two principal aims of this study were, firstly, to outline the socio-demographics of the maritime communities and examine how variant linguistic features may have developed and spread among these communities, and, secondly, to generate baseline data on the characteristic features of Ship English. The newly-identified characteristics of Ship English detailed here may now serve as an entry point for scholars to integrate this language variety into the discourse on dialect variation in Early Modern English period and the theories on pidgin and creole genesis.
Description based on print version record.
Language Science Press 2018-2020
Keywords: Language Arts & Disciplines / Alphabets & Writing Systems; Language arts; Electronic books